The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s12243-015-0473-8
|View full text |Cite
|
Sign up to set email alerts
|

A DTN-based architecture for public transport networks

Abstract: Delay/disruption-tolerant networking has been exploited in a variety of communication scenarios to provide basic delay-tolerant Internet services. In this paper, we propose a delay/disruption-tolerant networking (DTN)-based architecture for dense urban environments that exploits the existing infrastructure of public transport networks to provide Internet services through applications that can withstand certain delays without significantly affecting user experience. To achieve data delivery within the delay tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Hence, any unsent data was stored for future flights to reduce the end-to-end latency of the delivered message. Focusing on urban environments, authors in [43] introduced a reference routing protocol for DTN-capable nodes, aiming to extend the Internet coverage in highly-dense environments, while in [44], DTN applications in existing infrastructure of public transport networks were investigated. Moreover, the work by [45] concentrated on practical experimentation to validate the effectiveness of DTN solutions in different scenarios, considering the routing in space.…”
Section: Related Workmentioning
confidence: 99%
“…Hence, any unsent data was stored for future flights to reduce the end-to-end latency of the delivered message. Focusing on urban environments, authors in [43] introduced a reference routing protocol for DTN-capable nodes, aiming to extend the Internet coverage in highly-dense environments, while in [44], DTN applications in existing infrastructure of public transport networks were investigated. Moreover, the work by [45] concentrated on practical experimentation to validate the effectiveness of DTN solutions in different scenarios, considering the routing in space.…”
Section: Related Workmentioning
confidence: 99%
“…Their results provide a starting point for future research. Also, [3], [11][12][13][14][15][16][17][18] study data delivery over a bus network, similar to our research, but focuses on routing methods. As far as we know, there is not any known research on transmission scheduling method on a data port to meet userspecified delay constraints for large data object delivery over public transportations systems.smart mobile device sends/receives data within user's tolerant delay by using Wi-Fi as much as possible.…”
Section: Related Workmentioning
confidence: 99%
“…Examples include buses and rails, among others. References [3,4] reported that a similar approach that relies on the use of "data mule" carriers to extend the Internet connectivity in a rural area. We believe that the "data mule" concept can be leveraged to support delay-constrained transport of large-sized data objects via public transportation facilities.…”
Section: Introductionmentioning
confidence: 99%
“…It is one subtype of DTN, where nodes (vehicles) store and carry network data while waiting for opportunities to forward it. Komnios et al [3] introduced a CARPOOL+ routing technique of public transport by providing hotspot internet connectivity to all users and prior knowledge of their contacts. Similar work has been presented in [4], the author considered data center as a central point to pick up and deliver significant amount of data using public transport.…”
Section: Introductionmentioning
confidence: 99%